A COMPENSATING DIFFERENTIAL APPROACH TO VALUING THE SOCIAL BENEFIT OF MINOR LEAGUE BASEBALL. (7th August 2014) - Agha, Nola; Coates, Dennis
<x xml:space="preserve">Abstract</x> This research utilizes a compensating differential framework to measure the social benefits of minor league baseball teams. Consistent with findings at the major league level, individual housing observations from 138 metropolitan areas between 1993 and 2005 show that affiliated teams are associated with a significant 6 to 8% increase in rents in mid‐sized markets ranging from 0.4 to 1.4 million people. On the other hand, independent teams and stadiums are associated with insignificant effects on rents. The positive effect of affiliated minor league teams suggests they are a valuable urban amenity that can contribute to local quality of life. (JEL H23, H41, H71, R50, L83)